Self‐X Materials and Structures in Nature and Technology: Bio‐inspiration as a Driving Force for Technical Innovation. (September 2015) - Speck, Thomas; Knippers, Jan; Speck, Olga; Menges, Achim
<x xml:space="preserve">Abstract</x> Over the course of 3.8 billion years of biological evolution, nature has found the answers to many engineering problems. The aim of biomimetics is to analyse and tap biology's potential as a huge reservoir for innovative solutions. Thomas Speck, Professor and Director of the Plant Biomechanics Group (PBG) at the University of Freiburg and the Freiburg Centre for Interactive Materials and Bioinspired Technologies (FIT), Jan Knippers, Professor and Head of the Institute of Building Structures and Structural Design (ITKE) at the University of Stuttgart, and Olga Speck, a researcher at the PBG, scientific coordinator of FIT and manager of the Competence Network Biomimetics at Freiburg, explain how biological material systems with self‐x properties are cost‐efficient, multifunctional, and can be environmentally friendly; and with several billion trial runs, have surely stood the test of time.